2018
DOI: 10.1007/s11357-018-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system as a target for aging and obesity-related cardiovascular diseases

Abstract: Chronic sympathetic nervous system overactivity is a hallmark of aging and obesity and contributes to the development of cardiovascular diseases including hypertension and heart failure. The cause of this chronic sympathoexcitation in aging and obesity is multifactorial and centrally mediated. In this mini-review, we have provided an overview of the key and emerging central mechanisms contributing to the pathogenesis of sympathoexcitation in obesity and healthy aging, specifically focusing on hypertension. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 98 publications
(77 reference statements)
2
56
1
2
Order By: Relevance
“…[12] Insulin resistance and subsequent hyperinsulinemia have been reported to activate the sympathetic nervous and the renin angiotensin systems resulting in endothelial dysfunction. [34,35] With reference to Laplace's law, high BP and obesity could trigger cardiac remodeling through hemodynamic and these humoral mechanisms and the thickening of cardiac wall may occur through collagen deposits. [36] Mehta et al in the Dallas Heart Study found LVH to be an independent risk factor for subclinical atherosclerosis diagnosed by cardiac MRI, coronary artery calcium, and C-reactive protein measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Insulin resistance and subsequent hyperinsulinemia have been reported to activate the sympathetic nervous and the renin angiotensin systems resulting in endothelial dysfunction. [34,35] With reference to Laplace's law, high BP and obesity could trigger cardiac remodeling through hemodynamic and these humoral mechanisms and the thickening of cardiac wall may occur through collagen deposits. [36] Mehta et al in the Dallas Heart Study found LVH to be an independent risk factor for subclinical atherosclerosis diagnosed by cardiac MRI, coronary artery calcium, and C-reactive protein measurements.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IGF-1 promotes neuronal cell survival and repair, neurogenesis, synaptogenesis, cerebrovascular integrity (Ashpole et al 2015;Logan et al 2018;Sonntag et al 2013;Labandeira-Garcia et al 2017), and autophagic function in cortical neurons (Renna et al 2013), all of which could favorably impact possible underlying contributors to age-related cognitive decline, as well as neurological disease. It has to be recognized that age-dependent IGF-1 decline or IGF-1 deficiency may also impact aging through modulation of autonomic nervous system (Balasubramanian et al 2019). Interestingly, low IGF-1 levels have been associated with subsequent risk for vascular dementias (Quinlan et al 2017), while IGF-1 deficiency in young animals has been shown to impair cerebrovascular function and exacerbate hypertension-induced cerebrovascular microhemorrhages (Sonntag et al 2013;Tarantini et al 2017;Toth et al 2015).…”
Section: Gh/igf-1 Deficiency and The Nervous Systemmentioning
confidence: 99%
“…Tonic central nervous system sympathetic nerve firing helps maintain resting vasomotor tone. 1 The SNS is involved in regulation of renal functions, metabolism, and blood pressure through altering the arterial baroreflex. 2 Chronic SNS activity can cause pathological conditions such as hypertension, 3 renal failure, 4 endothelial dysfunction, 5 diastolic dysfunction, 6 increases in ventricular and aortic wall thickness, 7 and metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, there is a tendency for only specific target organs to be affected by changes in SNS activation to have a ''sympathetic signature'' depending on its source: heart failure leads to increased kidney SNS activity, but not in the gut. 1 Aging as well as obesity has been known to alter the SNS, especially through increased activation observed in cardiovascular diseases such as hypertension and heart failure. It has been speculated that cell senescence may be a key factor linked to activation of the SNS, although specifics remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation